Resolver-signal demodulator for variable frequency excitation signals - Kaewpoonsuk, Anucha; Rerkratn, Apinai; Riewruja, Vanchai (My University, 2014)
An alternative approach to implement the resolver-signal demodulator is presented in this paper. The realization technique utilizes the phase shift behavior of an all-pass filter connected with a designed logic circuit to generate the control signals for sub-circuits. The proposed demodulator produces two output signal voltages, which are the sine and cosine envelopes of resolver-shaft angle without low-pass filter circuit. Experimental results verifying the performance of the proposed circuit are closely agreed with the expected values. © 2014 ISSN 1881-803X.
Keywords: All-pass filter; Demodulator; Envelope detector; Resolver; Resolver converter